Association analysis of calpain 10 gene variants/haplotypes with gestational diabetes mellitus among Mexican women - Castro-Martínez, Anna Gabriela; Sánchez-Corona, José; Vázquez-Vargas, Adriana Patricia; García-Zapién, Alejandra Guadalupe; López-Quintero, Andres; Villalpando-Velazco, Héctor Javier; Flores-Martínez, Silvia Esperanza (Cellular and Molecular Biology, 2018)
Gestational diabetes mellitus (GDM) is a metabolically complex disease with major genetic determinants. GDM has been associated with insulin resistance and dysfunction of pancreatic beta cells, so the GDM candidate genes are those that encode proteins modulating the function and secretion of insulin, such as that for calpain 10 (CAPN10). This study aimed to assess whether single nucleotide polymorphism (SNP)-43, SNP-44, SNP-63, and the indel-19 variant, and specific haplotypes of the CAPN10 gene were associated with gestational diabetes mellitus. We studied 116 patients with gestational diabetes mellitus and 83 women with normal glucose tolerance. Measurements of anthropometric and biochemical parameters were performed. SNP-43, SNP-44, and SNP-63 were identified by polymerase chain reaction (PCR)-restriction fragment length polymorphisms, while the indel-19 variant was detected by TaqMan qPCR assays. The allele, genotype, and haplotype frequencies of the four variants did not differ significantly between women with gestational diabetes mellitus and controls. However, in women with gestational diabetes mellitus, glucose levels were significantly higher bearing the 3R/3R genotype than in carriers of the 3R/2R genotype of the indel-19 variant (p = 0.006). In conclusion, the 3R/3R genotype of the indel-19 variant of the CAPN-10 gene influenced increased glucose levels in these Mexican women with gestational diabetes mellitus.